Sinner or Saint?: Nck Adaptor Proteins in Vascular Biology - Alfaidi, Mabruka; Scott, Matthew L.; Orr, Anthony Wayne (Frontiers in Cell and Developmental Biology, 2021)
The Nck family of modular adaptor proteins, including Nck1 and Nck2, link phosphotyrosine signaling to changes in cytoskeletal dynamics and gene expression that critically modulate cellular phenotype. The Nck SH2 domain interacts with phosphotyrosine at dynamic signaling hubs, such as activated growth factor receptors and sites of cell adhesion. The Nck SH3 domains interact with signaling effectors containing proline-rich regions that mediate their activation by upstream kinases. In vascular biology, Nck1 and Nck2 play redundant roles in vascular development and postnatal angiogenesis. However, recent studies suggest that Nck1 and Nck2 differentially regulate cell phenotype in the adult vasculature. Domain-specific interactions likely mediate these isoform-selective effects, and these isolated domains may serve as therapeutic targets to limit specific protein-protein interactions. In this review, we highlight the function of the Nck adaptor proteins, the known differences in domain-selective interactions, and discuss the role of individual Nck isoforms in vascular remodeling and function.